Multi-Institutional Collaboration in Human Resource Development at Madrasah Ibtidaiyah Negeri (MIN) 3 Deli Serdang - Supriatin, Supriatin; Abri Harahap, Muhammad; Hamonangan Harahap, Domu; Hutahuruk, Alpian (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This article discusses improving the quality of education through multi-institutional collaboration with a case study at MIN 3 Deli Serdang. This study aims to analyze and describe HR management in this Islamic educational institution. This research uses a qualitative approach with a case study method. Data were collected through observation, documentation, and structured interviews. The results show that collaboration between madrasahs and the government, as well as the private sector and community, significantly improves the quality of education and human resource development (HRD). This collaboration improves teachers' professional competence and strengthens community trust in madrasahs. The study also highlights the critical role of madrasah principals in HR management, from procurement to educator development. Appropriate task placement and systematic coaching programs, such as regular meetings, training, seminars, and supervision, support the improvement of teachers' professionalism. The madrasah principal also motivates and facilitates teachers' career development and improves their welfare, especially for honorary teachers. This research provides recommendations for Islamic education institutions to strengthen multi-agency collaboration in human resource development. Effective collaboration can create a conducive environment for the growth and capacity development of educators and learners, improve the quality of teaching and learning, and increase the nation's competitiveness at the global level.